Development of empirical models to predict latent heat exchange performance for hollow fiber membrane-based ventilation system. (August 2022) - Cho, Hye-Jin; Cheon, Seong-Yong; Jeong, Jae-Weon
Highlights: A hollow fiber membrane-based ventilation system is proposed. Experiments were conducted using a membrane-based latent heat exchange module. Empirical models were developed to predict the latent heat exchange performance. Guidelines for implementation of the empirical models are provided. The proposed ventilation system showed enhanced latent heat exchange performance. Abstract: In this study, a hollow fiber membrane-based dual-core ventilation system is proposed to reduce space heating and cooling energy requirements. Simple prediction models were developed for the seasonal latent heat exchange performances of the proposed system. A mock-up model of the hollow fiber membrane module that serves as a latent heat exchanger in the proposed system was fabricated. A total of 32 experimental sets for the cooling and heating seasons were designed based on five operating parameters (outdoor air temperature and corresponding relative humidity, room air temperature and corresponding relative humidity, and outdoor air face velocity). The R-squared values of the derived models exceeded 96%, and the models were validated using additional measured data. Empirical correlations to predict the latent and sensible effectiveness were derived based on the response surface methods. A sensitivity analysis of each operating parameter on the latent heat exchange performance of the hollow fiber membrane module was performed. Finally, a guideline for the implementation of the developed models for energy simulation in building applications was presented. The proposed ventilation system improved the energy saving over that of the conventional energy recovery ventilator and reduced the ventilation load by 54.8% and 19.9% in summer and winter, respectively.